2020
DOI: 10.1021/acsnano.0c02396
|View full text |Cite
|
Sign up to set email alerts
|

Lower Critical Solution Temperature-Driven Self-Coacervation of Nonionic Polyester Underwater Adhesives

Abstract: To enable attachment to underwater surfaces, aquatic fauna such as mussels and sandcastle worms utilize the advantages of coacervation to deliver concentrated protein-rich adhesive cocktails in an aqueous environment onto underwater surfaces. Recently, a mussel adhesive protein Mfp-3s, was shown to exhibit a coacervation-based adhesion mechanism. Current synthetic strategies to mimic Mfp-3s often involve complexation of oppositely charged polymers. Such complex coacervates are more sensitive to changes in pH a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(50 citation statements)
references
References 58 publications
0
50
0
Order By: Relevance
“…It should be noted that the micelles in neutral environment are positively charged, which may contribute to the capability of micelles to coat tooth surface and promote bacterial adhesion by electrostatic adsorption. Previous studies found many factors, including energy, charge, composition, stiffness, and hydrophobicity of tooth surface ( Belas, 2014 ; Song et al, 2015 , 2017 ; Teschler et al, 2015 ), as well as size, charge, and ionic strength of micelles ( Paula and Koo, 2017 ; Narayanan et al, 2020 ; Li and Liu, 2021 ), can affect the binding between micelles and tooth surfaces. These binding-promoting properties of micelles should be further studied to improve their clinical application potential.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that the micelles in neutral environment are positively charged, which may contribute to the capability of micelles to coat tooth surface and promote bacterial adhesion by electrostatic adsorption. Previous studies found many factors, including energy, charge, composition, stiffness, and hydrophobicity of tooth surface ( Belas, 2014 ; Song et al, 2015 , 2017 ; Teschler et al, 2015 ), as well as size, charge, and ionic strength of micelles ( Paula and Koo, 2017 ; Narayanan et al, 2020 ; Li and Liu, 2021 ), can affect the binding between micelles and tooth surfaces. These binding-promoting properties of micelles should be further studied to improve their clinical application potential.…”
Section: Resultsmentioning
confidence: 99%
“…Especially, 30PVPh/ PEOX raises the adhesion strength to 0.57 MPa, exhibiting high adhesion strength in a wet environment compared with other wet adhesives in the literature (Figure 7h). [45][46][47][48][49][50][51] The less moisture absorption of 30PVPh/PEOX is believed to be the main reason for the adhesion strength in wet conditions.…”
Section: Mechanical Strengthmentioning
confidence: 99%
“…Therefore, it is a big challenge to develop biocompatible water-resistant adhesives with strong adhesion strength in a wet environment for practical applications in the adhesion science and technology. [12][13][14][15][16][17] In nature, a myriad of living organisms, such as sandcastle worms and mussels, can secrete sticky mucus to adhere to different surface of substrate. [18,19] Especially, mussels could secrete mussel adhesion proteins (MAPs) to anchor many materials firmly in wet conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is a big challenge to develop biocompatible water‐resistant adhesives with strong adhesion strength in a wet environment for practical applications in the adhesion science and technology. [ 12–17 ]…”
Section: Introductionmentioning
confidence: 99%